Epidermolysis Bullosa with Congenital Absence of Skin: A Report of Two Cases - Trishala Shirahatti; H. Bangaru; Sathish Shankar; Rithu Manoj; Amruta Shirahatti (Clinical Dermatology Review)
Epidermolysis bullosa (EB) with congenital absence of skin, also known as aplasia cutis congenita (ACC) type VI, is characterized by congenital localized absence of skin, nail abnormalities, and blistering of the skin and mucosa. ACC is classified based on the location and pattern of the absence of skin, the presence of associated malformations, and the mode of inheritance. We report two sporadic cases of EB with congenital absence of skin who presented with blistering of the skin and mucosa, localized absence of skin, and nail dystrophy without systemic involvement. The first case succumbed to the disease, whereas the second case survived with conservative management.